Influence of Renal Artery Variants, Number, Location, and Degree of Renal Artery Stenoses on the Atherosclerotic Burden of the Aorta. (1st October 2012) - Petersen, Johannes; Plaikner, Michaela; Nasseri, Parinaz; Rehder, Peter; Koppelstätter, Christian; Pauli, Guido F.; Glodny, Bernhard
Abstract : Objective: To determine the assumed influence of the number of renal arteries, the distribution and extent of renal artery stenosis (RAS), and the kidney length on calcified aortic atherosclerotic plaque burden. Methods: The computed tomographic angiographies of 1381 patients were analyzed retrospectively using a volumetric aortic calcium scoring method. The Spearman method was used to calculate the correlation between kidney length, number and diameter of renal arteries, as well as number, degree, and location of RASs on main or additional renal arteries with the extent of aortic atherosclerosis. Logistic regression analyses were conducted with the target variable "calcification present or absent." Results: Patients with multiple renal arteries (38.3%) had lower plaque volumes than patients without such variants (0.55 ± 0.97 vs 0.64 ± 1.06 mL; P < 0.05). Renal artery stenoses affected all renal vessels with equal frequency. The aortic calcium score correlated with the number of RASs ( P < 0.0001) and the maximum degree of RAS up to a threshold of 60%. Location of an RAS in the various renal arteries was irrelevant. In regression analyses, the presence of RAS (Wald = 5.523), the degree of RAS (Wald = 6.251), and age (Wald = 223.1) were positive predictors of the aortic calcium score, whereas kidney length (Wald = 9.564) proved to be a negative predictor. Conclusion: The aortic calcium score correlates with both the number of RASs and the maximum degree of RAS up to a threshold of 60% but correlates inversely with the number of renal arteries. Renal artery stenosis affects all renal vessels with equal frequency, and this finding should be considered in screening procedures.